2016
DOI: 10.1093/humrep/dew083
|View full text |Cite
|
Sign up to set email alerts
|

Patients with multiple morphological abnormalities of the sperm flagella due toDNAH1mutations have a good prognosis following intracytoplasmic sperm injection

Abstract: None of the authors have any competing interest. This work is part of the project 'Identification and Characterization of Genes Involved in Infertility (ICG2I)', funded by the program GENOPAT 2009 from the French Research Agency (ANR) and the MAS-Flagella project, financed by the French ANR and the Direction Générale de l'Offre de Soins (DGOS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 23 publications
4
64
0
Order By: Relevance
“…This abnormal sperm flagella phenotype was previously reported as dysplasia of the fibrous sheath or short/stump tail syndromes and occurs in more than 1 per 10 000 to 20 000 births . Patients with this phenotype could not achieve spontaneous pregnancy or fertilization in vitro, but a high success rate of intracytoplasmic sperm injection could be observed in some individuals with MMAF …”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…This abnormal sperm flagella phenotype was previously reported as dysplasia of the fibrous sheath or short/stump tail syndromes and occurs in more than 1 per 10 000 to 20 000 births . Patients with this phenotype could not achieve spontaneous pregnancy or fertilization in vitro, but a high success rate of intracytoplasmic sperm injection could be observed in some individuals with MMAF …”
Section: Introductionmentioning
confidence: 79%
“…[4][5][6] Patients with this phenotype could not achieve spontaneous pregnancy or fertilization in vitro, but a high success rate of intracytoplasmic sperm injection could be observed in some individuals with MMAF. 7 Previous studies demonstrated that MMAF was caused by genetic defects in several testis-specific genes. 1 Biallelic mutations in DNAH1, which encode an axonemal inner arm dynein, are responsible for 28%-44% of all MMAF patients.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported an increased rate of aneuploidy and a poor sperm nuclear quality related to sperm flagellar abnormalities, which could impede ICSI outcome (37). However, MMAF patients with DNAH1 mutations combine low aneuploidy rates and a good nuclear sperm quality leading to good ICSI results (106). Of course we cannot consider that it is the presence of DNAH1 mutations which are responsible for the good nuclear quality of the sperm but merely that many others patients with different defects do not have such good parameters and do not perform as well following ICSI.…”
Section: Multiple Morphological Abnormalities Of the Sperm Flagella (mentioning
confidence: 99%
“…No success of spontaneous pregnancy or conventional in vitro fertilization has been previously reported for MMAF, but individuals with MMAF have had a good prognosis after intracytoplasmic sperm injection. 9 Previous studies on genetic mutants in model organisms have revealed genetic contributions to flagellar motility defects. 2,[10][11][12][13][14] So far, mutations in only three genes, AKAP4 (MIM: 300185), CCDC39 (MIM: 613798), and DNAH1 (MIM: 603332), have been formally identified to cause MMAF in humans.…”
Section: Introductionmentioning
confidence: 99%